Factors governing enforcement of environmental law - Ansari, Abdul Haseeb; Eishan Jan, Mohammad Naqib (2016)
In spite of existence of several hundred treaties and state legislations, for enforcing them and original, for abatement and control of degradation of the environment and conservation of the biodiversity, a significant component of it, the condition of the environment around the world became bad to worst. Because of that, people are suffering and the environment is degrading. The laws at both the levels are being amended from time to time with a prime object for reversing the situation. But they have utterly failed even to stabilize the situation. To make a viable law is one thing, but to make it work requires its proper enforcement with the help of preventive and punitive measures. In environmental matters, as penalty does not always work, exploring factors, including low penalty, responsible for creating impediments in enforcement have to be properly investigated and discussed. The paper investigates into possible reasons for weakening of enforcement of environmental laws, discusses them and offers suggestions for proper enforcement.